The Interplay of Birth, Action, and Chance: Vedic Insights and Modern Interpretations on Life’s Determinants - Roy, Arindam (Journal of Social Science and Humanities, 2026)
This article explores the profound influence of birth, action, and chance on human life, drawing from both ancient Vedic teachings and contemporary observations. It delves into the three key determinants Janma birth, Karma action, and Bhaga chance and examines how these factors shape individual destinies. By integrating insights from the Vedas with modern sociological and genetic studies, the article highlights the enduring relevance of these concepts in understanding lifes dynamics. It also discusses the implications of these determinants in the context of societal structure, individual opportunities, and the randomness of chance, providing a comprehensive analysis of how personal outcomes are shaped by a complex interplay of predetermined and random factors.